Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, dan Sales Growth Terhadap Penghindaran Pajak - Santoso, Ferren; Purwaningsih, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study investigates in depth how profitability, debt-to-asset ratio (leverage), business scale (firm size), and sales growth rate affect tax avoidance practices in companies listed in the LQ45 index during the period 2020 to 2023. Using quantitative methods and analyzing secondary data from 80 companies, the results of the study show that overall, these four factors significantly affect companies' decisions to avoid taxes. Data analysis in this study using the SPSS Statistics application. Furthermore, partial analysis of profitability and firm size has a significant negative and positive effect on tax avoidance, respectively. Meanwhile, leverage and sales growth do not have a significant effect. These findings provide a better understanding of the factors that drive LQ45 companies in Indonesia to engage in tax avoidance practices, as well as providing valuable contributions to the development of literature in this field.